(untitled) (Kronika Bydgoska, 2010)
The article presents the involvement of Bydgoszcz athletes in celebrations of national holidays in the Stalinist period. The main emphasis is put on the celebrations of the two most important holidays in the calendar of the State govemed by communists, i.e.May 1 and July 22, i.e. the name day and the birthday of the system. It describes their participation in sports column parades, making commitments on the occasion of holidays, and playing occasional sports competitions. In these celebrations athletes occupied a special place sińce they contributed to making often boring ceremonies attractive, and they were great carriers and propagators of such ideas as fight for peace, communism and others. Anyway, they are still used this way not only in totalitarian States.